1985
DOI: 10.2307/1130460
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparisons of Developmental Dyslexia in Italy and the United States

Abstract: This study was designed to examine whether the phonetic regularity of a language can significantly influence the prevalence and pattern of developmental dyslexia. Demographically matched samples of fifth-grade children in Italy (N = 448) and the United States (N = 1,278) were evaluated to identify children with specific reading disabilities. Reading disabled children with average intelligence were compared to normal controls on a series of neuropsychological tests to evaluate specific cognitive deficits associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
9

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(64 citation statements)
references
References 10 publications
4
51
0
9
Order By: Relevance
“…Likewise, Wydell and Butterworth (1999) showed that orthographic knowledge in Japanese did not contribute to reading and spelling in L2 English. Such findings support the SDH (Liberman et al, 1974;Lindgren et al, 1985).…”
Section: Transfer Between Logographic Languages and Englishsupporting
confidence: 82%
See 4 more Smart Citations
“…Likewise, Wydell and Butterworth (1999) showed that orthographic knowledge in Japanese did not contribute to reading and spelling in L2 English. Such findings support the SDH (Liberman et al, 1974;Lindgren et al, 1985).…”
Section: Transfer Between Logographic Languages and Englishsupporting
confidence: 82%
“…Identical findings were reported regarding Circassian-English (Abu-Rabia, 1997b), Dutch-English (Morfidi et al, 2007) Hebrew-English (Shimron & Sivan, 1994), and Korean-English (Wang, Koda, & Perfetti, 2003). These findings support the SDH (Liberman et al, 1974;Lindgren et al, 1985), i.e., that orthographic skills are not transferred between languages but are rather language-specific.…”
Section: Transfer Between Alphabetic Languages and Englishsupporting
confidence: 74%
See 3 more Smart Citations